On the Notation of Catastrophes in the Framework of Bonding Evolution Theory: Case of Normal and Inverse Electron Demand Diels-Alder Reactions - Ayarde Henriquez, Leandro (My University, 2022)
This paper generalizes very recent and unexpected findings [J. Phys. Chem. A, 2021, 125, 5152–5165] regarding the known “direct- and inverse-electron demand” Diels-Alder mechanisms. Application of bonding evolution theory indicates that the key electron rearrangement associated with significant chemical events (e. g., the breaking/forming processes of bonds) can be characterized via the simplest fold polynomial. For the CC bond formation, neither substituent position nor the type of electronic demand induces a measurable cusp-type signature. As opposed to the case of [4+2] cycloaddition between 1,3-butadiene and ethylene, where the two new CC single bonds occur beyond the transition state (TS) in the activated cases, the first CC bond occurs in the domain of structural stability featuring the TS, whereas the second one remains located in the deactivation path connecting the TS with the cycloadduct.
PUBLISHED